Pengaruh Profitability, Liquidity, Free Cash Flow, dan Firm Size Terhadap Kebijakan Dividend Payout Ratio(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Shoviyana, Evi, Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2017)
Dividend policy is very important to determine the placement of profit, which is between paying to shareholders and reinvested in the company. One general corporate purpose is to maximize shareholder wealth. On the other hand, the presence of retained earnings is one of the most important sources of funds to finance the growth of the company in order to survive. The purpose of this study was to examine the effect of Profitability (ROA), Likuidity (CR), Free Cash Flow, and Firm Size of the Dividend Payout Ratio on manufacturing companies listed in Indonesia Stock Exchange from 2010 to 2013. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange in the year 2012-2015 and the dividends consecutively during the study period. The sampling method with a purposive sampling corresponding predetermined criteria. The number of samples collected as many as 60. With the data outliers, the samples were 28 to 32. The data collected was analyzed by using data analysis conducted prior classic assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f, and the coefficient of determination. The results showed that the variables Profitability (ROA), Likuidity (CR), Free Cash Flow, and Firm Size effect on Dividend Payout Ratio. This suggests that Profitability (ROA), Likuidity (CR), Free Cash Flow, and Firm Size may affect the size distribution of Dividend Payout Ratio on manufacturing companies listed in Indonesia Stock Exchangefrom 2010 to 2013. Keywords:Profitability (ROA), Likuidity (CR), Free Cash Flow, Firm Size, Dividend Payout Ratio.